New Insights into the In Vitro Antioxidant Routes and Osteogenic Properties of Sr/Zn Phytate Compounds - Gerardo Asensio; Marcela Martín-; Rosa Ana Ramírez; Luis Rojo; Blanca Vázquez-Lasa (MDPI AG, 2023)
Sr/Zn phytate compounds have been shown interest in biomaterial science, specifically in dental implantology, due to their antimicrobial effects against Streptococcus mutans and their capacity to form bioactive coatings. Phytic acid is a natural chelating compound that shows antioxidant and osteogenic properties that can play an important role in bone remodelling processes affected by oxidative stress environments, such as those produced during infections. The application of non-protein cell-signalling molecules that regulate both bone and ROS homeostasis is a promising strategy for the regeneration of bone tissues affected by oxidative stress processes. In this context, phytic acid (PA) emerged as an excellent option since its antioxidant and osteogenic properties can play an important role in bone remodelling processes. In this study, we explored the antioxidant and osteogenic properties of two metallic PA complexes bearing bioactive cations, i.e., Sr2+ (SrPhy) and Zn2+ (ZnPhy), highlighting the effect of the divalent cations anchored to phytate moieties and their capability to modulate the PA properties. The in vitro features of the complexes were analyzed and compared with those of their precursor PA. The ferrozine/FeCl2 method indicated that SrPhy exhibited a more remarkable ferrous ion affinity than ZnPhy, while the antioxidant activity demonstrated by a DPPH assay showed that only ZnPhy reduced the content of free radicals. Likewise, the antioxidant potential was assessed with RAW264.7 cell cultures. An ROS assay indicated again that ZnPhy was the only one to reduce the ROS content (20%), whereas all phytate compounds inhibited lipid peroxidation following the decreasing order of PA > SrPhy > ZnPhy. The in vitro evaluation of the phytate's osteogenic ability was performed using hMSC cells. The results showed tailored properties related to the cation bound in each complex. ZnPhy overexpressed ALP activity at 3 and 14 days, and SrPhy significantly increased calcium deposition after 21 days. This study demonstrated that Sr/Zn phytates maintained the antioxidant and osteogenic properties of PA and can be used in bone regenerative therapies involving oxidative environments, such as infected implant coatings and periodontal tissues.